Selective encryption of video frames using the one-time random key algorithm and permutation techniques for secure transmission over the content delivery network - Murari T., Vijaya; K C, Ravishankar; M E, Raghu (Multimedia tools and applications, 2024)
In the last few years, the volume of internet traffic has increased enormously. A significant portion of the internet traffic is constituted by applications that stream multimedia data from one part of the world to another. The enormity of the video data requires the Content Delivery Network to distribute the content efficiently and securely among the consumers. The secure and authenticated distribution can be achieved by the end-to-end encryption of video. In this paper, one time random key algorithm and the algorithms and methods based on permutation techniques have been proposed to encrypt the video frames selectively and these encrypted frames are transmitted over the network along with the other video frames. The proposed encryption methods extract the colour channels like Red, Green and Blue from the video frames, and they are encrypted by applying row-column permutation cipher, One Time Pad cipher and row permutation cipher. Encryption of the video frames has been performed at two levels by combining the one-time random key algorithm and permutation techniques to provide security to the video. These encryption techniques have been applied on the twenty-five, thirty, and thirty-five, and so on, up to fifty per cent of the total frames available in the video. The experimental results, histogram analysis and parameters like average Peak Signal-to-noise Noise Ratio (PSNR) and Structural Similarity Index (SSIM) values measure the quality of the video obtained after the application of the proposed methods on the video to be transmitted over the network.